Formulasi Tindak Pidana Ekosida dalam Hukum Pidana Nasional Urgensi Pembaruan Hukum di Era Krisis Lingkungan Global - Jachrisdo Damanik; Methodius Kossay; Mangaratua Naibaho; Dame Pandiangan (Universitas Sains dan Teknologi Komputer, 2026)
The massive scale of environmental destruction globally highlights the urgent need for a stronger legal response, particularly through criminal law. This research aims to formulate the crime of ecocide within Indonesia's national criminal law framework by adapting international principles while aligning with the fundamental doctrines of Indonesian law. Employing a normative legal research method and comparative analysis, this study reveals a significant legal gap in the current regulatory system, which inadequately addresses large-scale ecosystem damage. A conceptual model for the formulation of ecocide crimes is proposed, including the definition of criminal elements, the scope of liable subjects, and the appropriate sanctions. The results contribute to the academic discourse by offering a structured and applicable legal framework, while practically providing policymakers with a concrete foundation for legal reforms that respond effectively to the global environmental crisis.